Operationalising sustainability? Why sustainability fails as an investment criterion for safeguarding the future. Issue 1 (15th November 2022) - Friederich, Simon; Symons, Jonathan
Abstract: Policy instruments promoting sustainability, such as investment taxonomies, are playing an increasing role in guiding the allocation of financial resources internationally. But can policy instruments define sustainability in ways that are both operational (i.e. assessable via replicable procedures) and which specify practices that can reliably be expected to enhance future generations' welfare? This paper analyses candidate definitions of sustainability and identifies a dilemma: while various definitions identify a 'capital' variable whose value can indeed be determined empirically; we have no reason to assume that preservation of any specific capital variable will maximise expected future welfare. By contrast, sustainability can be defined 'dynamically' in terms of activities that will, on expectation, lead to future developmental trajectories with high welfare. But, as we show through discussion of concrete examples, 'dynamic sustainability' cannot readily be operationalised. We conclude that what qualifies as 'sustainable' will remain a subject of political dispute and that authoritative comprehensive assessments of 'sustainability' will remain chimeric. We suggest that selecting a narrow class of specific measures, such as of life‐cycle greenhouse gas emissions, might lead to more effective and less contentious approaches to resource allocation.